The Black Belt - Allen Tullos (Southern Spaces, 2004)
This essay considers the historical-geographical Black Belt, beginning as a rich, dark-soil, cotton-growing region of Alabama occupied by slaveholders in the 1820s and 30s, and becoming, over time, a more generalized designation for a region or place with a majority black population. By the late twentieth century, the Alabama Black Belt as a region of insurgent African American aspirations made a strong claim to take over the meaning of the term from its older and other senses.